2016
DOI: 10.1002/osp4.75
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms in women's midlife in relation to their body weight before, during and after childbearing years

Abstract: SummaryObjectiveThis study aimed to examine how weight and weight changes related to pregnancy were associated with depressive symptoms 11–16 years after childbirth.MethodWe followed 16,998 first‐time mothers from the Danish National Birth Cohort up till 16 years after birth and estimated associations between depressive symptoms and pre‐pregnancy body mass index (BMI) (kg m−2), weight changes in different time periods, and BMI‐adjusted waist circumference 7 years after birth (WCBMI, cm). Depressive symptoms we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 49 publications
2
8
1
Order By: Relevance
“…They also studied if waist circumference (WC) adjusted for BMI (WC BMI ) 7 years after childbirth (as an indicator for abdominal adiposity) was associated with depressive symptoms. The authors found that women with a larger waist circumference than predicted by their BMI reported more depressive symptoms than women with a WC in accordance with their BMI [47]. In our study, we estimated a 9% misclassi cation rate among the women with obesity.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…They also studied if waist circumference (WC) adjusted for BMI (WC BMI ) 7 years after childbirth (as an indicator for abdominal adiposity) was associated with depressive symptoms. The authors found that women with a larger waist circumference than predicted by their BMI reported more depressive symptoms than women with a WC in accordance with their BMI [47]. In our study, we estimated a 9% misclassi cation rate among the women with obesity.…”
Section: Discussionsupporting
confidence: 58%
“…The use of BMI to classify individuals and its utility as a measure of health has been consistently contested in the literature [45,46]. A recent Danish study looked at the association between weight and depressive symptoms in a group of women followed for up to 16 years after their rst birth [47]. They also studied if waist circumference (WC) adjusted for BMI (WC BMI ) 7 years after childbirth (as an indicator for abdominal adiposity) was associated with depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…They also studied if waist circumference (WC) adjusted for BMI (WC BMI ) 7 years after childbirth (as an indicator for abdominal adiposity) was associated with depressive symptoms. The authors found that women with a larger waist circumference than predicted by their BMI reported more depressive symptoms than women with a WC in accordance with their BMI [46]. In our study, we estimated a 9% misclassi cation rate among the women with obesity.…”
Section: Discussionsupporting
confidence: 58%
“…The use of BMI to classify individuals and its utility as a measure of health has been consistently contested in the literature [44,45]. A recent Danish study looked at the association between weight and depressive symptoms in a group of women followed for up to 16 years after their rst birth [46]. They also studied if waist circumference (WC) adjusted for BMI (WC BMI ) 7 years after childbirth (as an indicator for abdominal adiposity) was associated with depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][20][21][22] whereas among overweight reproductive age range from 5.9% to 38%. [10][11][12][13][14][15][20][21][22][23] Despite depression and overweight have many negative consequences on the mental health of reproductive-age women; no information on the degree to which normal and overweight women experienced depression, and its associated factors in Ethiopia. Therefore, this study aimed to assess and compare the prevalence of depression and associated factors among normal and overweight reproductive-age women in Debre Berhan town, Ethiopia.…”
Section: Introductionmentioning
confidence: 99%